Tendências de normalização na tradução para o inglês da obra As Mulheres de Tijucopapa - Grigoleto, Grace Gonçalves [UNESP]; Camargo, Diva Cardoso de [UNESP] (My University, 2011)
The present essay aims at observing possible tendencies of normalization by the translator Irene Matthews in the translation to English from As mulheres de Tijucopapo, by Marilene Felinto. The methodology employed is that of corpus-based translation studies (proposed by BAKER, 1993, 1995, 1996, 2000; SCOTT’s study concerning normalization, 1998; and CAMARGO’s research studies, 2005, 2007), and that of corpus linguistics (BERBER SARDINHA’s studies, 2003, 2004). The investigation was carried out by means of a combination of semi-manual and computerized analyses using the computer software WordSmith Tools. Based on Scott (1998), we analyzed the translation of five words considered to be preferred by the author, as well as their co-text, in relation to three normalization features. The final results obtained in this study show that the translator Irene Matthews tends to use strategies that may be identified as features of normalization.

O presente artigo tem por objetivo analisar possíveis tendências de normalização por parte da tradutora Irene Matthews na tradução para o inglês da obra As mulheres de Tijucopapo, de Marilene Felinto. A metodologia situa-se no campo dos estudos da tradução baseados em corpus (proposta de BAKER, 1993, 1995, 1996, 2000; estudos sobre normalização de SCOTT, 1998; e pesquisas de CAMARGO, 2005, 2007), e no da linguística de corpus (estudos de BERBER SARDINHA, 2003, 2004). A pesquisa foi realizada por meio de uma combinação de análises semimanuais e de análises computadorizadas com o auxílio do programa WordSmith Tools. Com base em Scott (1998), examinamos a tradução de cinco vocábulos considerados preferenciais da autora, juntamente com seu cotexto, em relação a três características de normalização. Os resultados finais mostram que Matthews tende a usar estratégias que podem ser identificadas como características de normalização.
Tendencies of normalization in the translation to English of As mulheres de Tijucopapo
Keywords: Tradução literária; Estudos de tradução baseados em corpus; Lingüística de Corpus; Literatura Brasileira traduzida; Normalização; Marilene Felinto